Development of STEAM-PJBL Integrated LKPD on Acid and Based Materials For Class XI SMA - Shella Dewanti Putri; Effendi Effendi (Journal of Educational Sciences, 2023)
This study aims to develop teaching materials in the form of Student Activity Sheets (LKPD) which are integrated in Science, Technology, Engineering, Arts and Mathematics – Project-Based Learning (STEAM-PjBL) on Acids and Bases material and are used to determine the level of validity and practicality of the LKPD that is used. developed. This research is a research (R&D) with a 4-D development model. This 4-D model has four stages, namely the stages of define, design, develop and disseminate. However, the dissemination stage was not carried out. This study used instruments in the form of content and construct validation questionnaires, teacher and student response questionnaires. This LKPD was validated by five experts consisting of a Chemistry lecturer (FMIPA UNP) and a chemistry teacher. The validation data obtained were analyzed using the v Aiken scale, while the practicality data were analyzed using a comparison of students' scores with students' maximum scores. Based on the validation questionnaire that has been analyzed, it can be concluded that the LKPD developed is valid with a v value of 0.86 with a very valid category. While the practicality of teachers and students obtained NP values of 0.85 and 0.89 with very practical categories.